Biomechanical predictors of ball velocity during punt kicking in elite rugby league kickers - Sinclair, J.; Taylor, P. J.; Atkins, S.; Hobbs, S. J. (International Journal of Sports Science & Coaching, 2016)
Punt kicking is integral to the attacking and defensive elements of rugby league and the ability to kick the ball with high velocity is desirable. This study aimed to identify important technical aspects of kicking linked to the generation of ball velocity. Maximal punt kicks were obtained from six elite rugby league kickers using a 10-camera motion capture system. Three-dimensional kinematics of the lower extremities was obtained. Regression analysis with ball velocity as criterion was used to identify the kinematic parameters associated with the development of ball velocity. The regression model yielded an adj R2¼0.76, p 0.01. Two parameters were identified: knee extension angular velocity of the kicking limb at impact (R2¼0.50) and peak flexion angular velocity of the kicking hip (R2¼0.26, p 0.01). It is conceivable that players may benefit from exposure to coaching and strength techniques geared toward the modification of kicking mechanics specific to this study.